Teaching ERP using an international inter-group collaborative learning environment - Rudra, Amit; Jaeger, B.; Aitken, Ashley; Chang, Vanessa (Monash University of Technology, 2009)
The goal of this research is to develop and evaluate a curriculum that teaches ERP concepts and skills using hands-on practical tasks in a globalised context. The curriculum employs Kolb's experiential learning cycle to facilitate student learning about the issues associated with internationalisation and globalisation of business operations and the use of ERP systems. A small pilot study was undertaken to test the assignment and logistical arrangements with some students undertaking an international inter-group collaboration. Students in Australia and Norway play alternating customer and vendor roles in business transactions recorded on a SAP ERP system. A pre- and post-survey (based on a previous instrument by Seethamraju) evaluated students' perceived knowledge gain across five different areas. The Norwegian students showed only a minor gain in perceived knowledge whilst the Australian students showed significant gains. Students involved in the inter-group (international) role play showed better understanding of the transactional aspects of business operations that those who did not.